The importance of macroalgae and associated amphipods in the selective benthic feeding of sister rockcod species Notothenia rossii and N. coriiceps (Nototheniidae) in West Antarctica - Barrera Oro, Esteban; Moreira, María Eugenia; Seefeldt, Meike Anna; Valli Francione, Mariano; Quartino, Maria Liliana (Polar Biology)
Studies on feeding selectivity in Antarctic fish with comparison between diet organisms and those available in the wild are scarce. We explored this issue in Notothenia rossii (NOR) and N. coriiceps (NOC) at Potter Cove in summer 2016 to test: (1) their preference among different benthic groups, primarily species of algae and amphipods and (2) differences between these nototheniids given their distinct morphology but their known similar general ecology in the fjords. The methodology included a comparative analysis of benthic organisms identified in the stomachs and those collected on macroalgal beds (Ivlev Index). Benthic amphipods, mainly Gondogeneia antarctica and Cheirimedon femoratus, followed by macroalgae, mainly Palmaria decipiens and Desmarestia spp., were the most important and frequent dietary items (IRI%) for both nototheniids. However, NOC was more herbivorous and fed more intensively on a wider diversity of benthic organisms such as certain algal-associated groups like gastropods and bivalves, whereas NOR fed on a greater proportion of epibenthic amphipods and other epibenthic prey. Although in the last three decades the physiognomy of the inner cove has been changed due to the retreat of the Fourcade Glacier, at our sampling site in the outer cove the abundance and vertical distribution of macroalgae did not show substantial changes compared with those reported in the literature in 1994–1996. Temporal differences in the feeding selectivity of NOC on amphipod species, between contemporary and historical samples, may be explained by variations in the assemblage of the algal-associated epifauna. We suggest factors that may have produced these changes. Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; ...